Chronic methamphetamine exposure produces a delayed, long‐lasting memory deficit. Issue 5 (8th February 2013) - North, Ashley; Swant, Jarod; Salvatore, Michael F.; Gamble‐george, Joyonna; Prins, Petra; Butler, Brittany; Mittal, Mukul K.; Heltsley, Rebecca; Clark, John T.; Khoshbouei, Habibeh
<x xml:space="preserve">Abstract</x> Methamphetamine (METH) is a highly addictive and neurotoxic psychostimulant. Its use in humans is often associated with neurocognitive impairment. Whether this is due to long‐term deficits in short‐term memory and/or hippocampal plasticity remains unclear. Recently, we reported that METH increases baseline synaptic transmission and reduces LTP in an ex vivo preparation of the hippocampal CA1 region from young mice. In the current study, we tested the hypothesis that a repeated neurotoxic regimen of METH exposure in adolescent mice decreases hippocampal synaptic plasticity and produces a deficit in short‐term memory. Contrary to our prediction, there was no change in the hippocampal plasticity or short‐term memory when measured after 14 days of METH exposure. However, we found that at 7, 14, and 21 days of drug abstinence, METH‐exposed mice exhibited a deficit in spatial memory, which was accompanied by a decrease in hippocampal plasticity. Our results support the interpretation that the deleterious cognitive consequences of neurotoxic levels of METH exposure may manifest and persist after drug abstinence. Therefore, therapeutic strategies should consider short‐term as well as long‐term consequences of methamphetamine exposure. Synapse 67:245–257, 2013. © 2012 Wiley Periodicals, Inc.